2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105325
|View full text |Cite
|
Sign up to set email alerts
|

Time of Stroke Onset in Coronavirus Disease 2019 Patients Around the Globe: A Systematic Review and Analysis

Abstract: Highlights Stroke cases continue to rise in the COVID-19 pandemic Stroke presents late in severe COVID-19 patients and early in mild cases Patients with large vessel occlusion were younger and had higher NIHSS Hypercoagulability and inflammation in COVID-19 are related to stroke Other cause should be considered as a stroke etiology in COVID-19 patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Other studies corroborate the high incidence of cryptogenic stroke, with time to stroke ranging from 0 to 65 days after onset of symptoms. 24 In our study, all cerebrovascular events occurred at a mean 46 days after diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 62%
“…Other studies corroborate the high incidence of cryptogenic stroke, with time to stroke ranging from 0 to 65 days after onset of symptoms. 24 In our study, all cerebrovascular events occurred at a mean 46 days after diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 62%
“…Multiple studies suggest that pro-inflammatory markers associated with COVID-19 infection, including D-dimer, IL-6, ferritin, and fibrinogen, may contribute to an inflammatory process mediating cerebrovascular accidents. One study found correlations with large vessel thrombosis and anterior circulation strokes[ 60 ], but more data and institutional collaboration of information are needed to understand the significance of the anatomic locality of strokes associated with COVID-19 infection. This multi-centered approach may elucidate future guidelines for certain patients, risk factors, or clinical findings unique to COVID-19 patients with neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient experienced his stroke within the 9-day period, from onset of COVID symptoms, that some authors described. 7 - 9 Other authors have reported large-vessel stroke in young COVID patients with limited risk factors; however, the stroke usually occurred at the onset of COVID illness before patients presented to the hospital and involved one vascular territory. 8 Malignant edema has complicated stroke in other patients, at times requiring hemicraniectomy, 9 but this occurred again with unilateral infarcts.…”
Section: Discussionmentioning
confidence: 99%